REFOCUSING THE RESPONSIVENESS REQUIREMENT - Shah, Seema (Bioethics, 2013)
Many guidelines for international research require that studies be responsive to host community health needs or health priorities. Although responsiveness possesses great intuitive and rhetorical appeal, existing conceptions are confusing and difficult to apply. Not only are there few examples of what research the responsiveness requirement permits and what it rejects, but its application can lead to contradictory results. Because of the practical difficulties in applying responsiveness and the danger that misapplying responsiveness could harm the interests of developing countries, we argue that responsiveness should be refocused in three ways: in terms of (1) who enforces it, (2) under what standard, and (3) in what cases. We conclude that responsiveness should be applied by host country officials at the policy level with the exercise of judgment when externally funded research threatens to displace scarce local resources.